Case report: Actinomycetoma caused by Nocardia aobensis from Lao PDR with favourable outcome after short-term antibiotic treatment. - Vongphoumy, I; Dance, D; Dittrich, S; Logan, J; Davong, V; Rattanavong, S; Blessmann, J (Public Library of Science, 2015)
BACKGROUND: Mycetoma is a neglected, chronic, localized, progressively destructive, granulomatous infection caused either by fungi (eumycetoma) or by aerobic actinomycetes (actinomycetoma). It is characterized by a triad of painless subcutaneous mass, multiple sinuses and discharge containing grains. Mycetoma commonly affects young men aged between 20 and 40 years with low socioeconomic status, particularly farmers and herdsmen. METHODOLOGY/PRINCIPAL FINDINGS: A 30 year-old male farmer from an ethnic minority in Phin District, Savannakhet Province, Lao PDR (Laos) developed a painless swelling with multiple draining sinuses of his right foot over a period of approximately 3 years. X-ray of the right foot showed osteolysis of tarsals and metatarsals. Aerobic culture of sinus discharge yielded large numbers of Staphylococcus aureus and a slow growing Gram-positive rod. The organism was subsequently identified as Nocardia aobensis by 16S ribosomal RNA gene sequencing. The patient received antimicrobial treatment with amikacin and trimethoprim-sulfamethoxazole according to consensus treatment guidelines. Although slight improvement was noted the patient left the hospital after 14 days and did not take any more antibiotics. Over the following 22 weeks the swelling of his foot subsequently diminished together with healing of discharging sinuses. CONCLUSION: This is the first published case of Actinomycetoma caused by Nocardia aobensis and the second case of Actinomycetoma from Laos. A treatment course of only 14 days with amikacin and trimethoprim-sulfamethoxazole was apparently sufficient to cure the infection, although long-term treatment up to one year is currently recommended. Treatment trials or prospective descriptions of outcome for actinomycetoma should investigate treatment efficacy for the different members of Actinomycetales, particularly Nocardia spp., with short-term and long-term treatment courses.